Impact of body composition analysis on male sexual function: A metabolic age study - Majzoub, Ahmad; Elbardisi, Haitham; Madani, Sarah; Leisegang, Kristian; Mahdi, Mohamed; Agarwal, Ashok; Henkel, Ralf; Khalafalla, Kareim; ElSaid, Sami; Arafa, Mohamed (Frontiers in Endocrinology, 2023)
Metabolic Age (MetAge) and body composition analysis may reflect an individual’s metabolic status, which is believed to influence male sexual and gonadal functions. Although erectile dysfunction (ED) and hypogonadism are increasingly prevalent with age, they are also detected among younger men. This study aims to assess the impact of MetAge and body composition on male sexual and gonadal status overall, and particularly in men younger than 40 years of age. This was a cross-sectional study of 90 male healthcare workers, between the ages of 18-55, randomly selected based on their corporation numbers. In addition to Bioelectric Impedance Analysis, subjects were requested to fill the International Index of Erectile Function questionnaire (IIEF-5) and to provide an early morning serum testosterone (T) sample. The mean participants’ age was 39.4 ± 9.4 years, MetAge was 45.54 ± 10.35 years, serum T level was 13.68 ± 4.49 nmol/L and BMI was 28.8 ± 4.7 kg/m2. Significant negative correlations were obtained between serum T, MetAge, body weight and fat composition. Significant negative correlations between the IIEF-5 score, MetAge, and fat composition, were only reported in subjects <40 years of age. Significantly lower T levels (p=0.002), significantly older MetAge (p=0.034), and higher BMI (p=0.044) and degree of obesity (p=0.042) were observed in participants <40 years with erectile dysfunction (ED) compared to their counterparts without ED. MetAge and body composition parameters significantly impact the androgenic state. ED in men <40 years is associated with lower T levels, older MetAge and higher BMI and degree of obesity.